Dopamine D1 receptor in the NAc shell is involved in delayed emergence from isoflurane anesthesia in aged mice. Issue 1 (22nd October 2020) - Zhang, Yi; Gui, Huan; Hu, Lang; Li, Chengxi; Zhang, Jie; Liang, Xiaoli
Abstract: Background: Delayed emergence after general anesthesia tends to occur in the elderly population, but the mechanism remains unclear. Apart from age‐related pharmacokinetic changes, the aging‐induced structural and functional alterations in the arousal‐promoting neural substrates should be considered. The nucleus accumbens (NAc) is a crucial arousal‐related nucleus, in which activating medium spiny neurons (MSNs) expressing dopamine D1 receptor (D1R) could facilitate the arousal from natural sleep. Meanwhile, the dopaminergic systems decline with aging in multiple brain regions. However, whether the age‐related decline in D1R in the NAc shell attenuates its arousal‐promoting capacity from general anesthesia remains to be elucidated. Methods: We first verified the delayed emergence from isoflurane anesthesia and examined the corresponding changes of electroencephalogram (EEG) power in aged mice. In turn, the arousal‐modulating capacity of D1R was characterized in the young and aged cohorts by microinjection of D1R agonist/antagonist into the NAc shell. Furthermore, to address the possible mechanism responsible for the attenuated arousal‐modulating capacity of the aged NAc, the expression of D1R in the NAc shell was measured and compared between young and aged mice. Results: Our data indicated that compared with young mice, the emergence time in aged mice was notably longer, while EEG power in δ band (1‐4Hz) was significantly higher and power in β band (12‐25Hz) was lower. Activating or inhibiting D1R in the NAc shell by microinjection D1R agonist/antagonist promoted or delayed the emergence process in young mice. Nevertheless, this modulation capacity of D1R in the NAc shell declined in aged mice, respectively. Meanwhile, downregulation of D1R expression in the NAc shell was detected in the aged brain. Conclusion: Together, these results suggest that aging attenuates the arousal‐modulating capacity of D1R in the NAc shell probably through downregulation of D1R expression therein, which may provide a potential explanation and a therapeutic target for increased sensitivity to anesthetics in the elderly patients. Abstract : Emergence time from isoflurane anesthesia was delayed and cortical EEG power was altered during the emergence process in aged mice. Activating or inhibiting D1R in the NAc shell promoted or delayed the emergence process in terms of behavior and EEG power. Nevertheless, the modulation capacity of D1R in the NAc shell declined with age, probably due to the age‐related downregulation of D1R in the NAc shell. These data may provide a potential pharmacodynamical explanation and a therapeutic target for delayed emergence from general anesthesia and increased sensitivity to anesthetics in elderly patients.